Emotionally Intelligent Next-Generation Touch-Controlled Prosthetic Hand - S., Abhirami J; R., Richard; T., Muhammed Ajilan P; S., Mahendran (Journal of Electronics and Informatics, 2024)
The research aims to develop an affordable and functional prosthetic hand with tactile feedback capabilities, addressing the challenges faced by individuals with upper limb differences. Through the integration of advanced sensing technologies such as EMG sensors and vibration motors, the prosthetic hand enables users to experience tactile sensations while grasping or interacting with objects. The design prioritizes modularity, adjustability, and lightweight materials to ensure a comfortable and customizable fit for a diverse range of users. Additionally, the prototype incorporates user-friendly interfaces and accessible components for ease of maintenance and repair. Through iterative testing and refinement, the proposed prosthetic hand seeks to provide a user-centered solution that enhances functionality, usability, and affordability in prosthetic hand technology. Ultimately, the prosthetic hand aims to empower individuals with upper limb differences by restoring dexterity and sensory perception, improving their quality of life, and fostering greater independence in daily activities.
Keywords: Prosthetic Hand; Tactile Feedback; EMG Sensors; Affordable; User-Centered